Youth Descriptions of Mental Health Needs and Experiences with School-based Services: Identifying Ways to Meet the Needs of Underserved Adolescents - DeFosset, Amelia R (J Health Care Poor Underserved, 2017)
While schools serve as a common entry point into mental health services for underserved youth, engagement of students in need of care remains a problem. Little is known about the ways schools can best address students’ mental health needs, especially from the perspective of youth who struggle to attend school, a vulnerable group with a high burden of mental health problems. A qualitative descriptive approach was used to analyze data from in-depth interviews with a sample of 18 youth with a history of school truancy and mental health problems. Analyses explored how youth expressed mental health symptoms, and their trajectories through, and perceptions of, school-based mental health services. Results suggest that participants experienced multiple, overlapping symptoms; only a portion had their needs addressed. The quality of relationships with school staff and the perceived efficacy of treatment affected service trajectories. Promising school-based approaches to address students’ mental health needs are discussed.